Impact of immunosuppressive and antifungal drugs on PBMC- and whole blood-based flow cytometric CD154+ Aspergillus fumigatus specific T-cell quantification - Page, Lukas; Lauruschkat, Chris D.; Helm, Johanna; Weis, Philipp; Lazariotou, Maria; Einsele, Hermann; Ullmann, Andrew J.; Loeffler, Juergen; Wurster, Sebastian (Medical Microbiology and Immunology, 2020)
Flow cytometric quantification of CD154+ mould specific T-cells in antigen-stimulated peripheral blood mononuclear cells (PBMCs) or whole blood has been described as a supportive biomarker to diagnose invasive mould infections and to monitor therapeutic outcomes. As patients at risk frequently receive immunosuppressive and antifungal medication, this study compared the matrix-dependent impact of representative drugs on CD154+ T-cell detection rates. PBMCs and whole blood samples from healthy adults were pre-treated with therapeutic concentrations of liposomal amphotericin B, voriconazole, posaconazole, cyclosporine A (CsA) or prednisolone. Samples were then stimulated with an Aspergillus fumigatus lysate or a viral antigen cocktail (CPI) and assessed for CD154+ T-helper cell frequencies. Specific T-cell detection rates and technical assay properties remained largely unaffected by exposure of both matrices to the studied antifungals. By contrast, CsA and prednisolone pre-treatment of isolated PBMCs and whole blood adversely impacted specific T-cell detection rates and caused elevated inter-replicate variation. Unexpectedly, the whole blood-based protocol that uses additional α-CD49d co-stimulation was less susceptible to CsA and prednisolone despite prolonged drug exposure in the test tube. Accordingly, addition of α-CD49d during PBMC stimulation partially attenuated the impact of immunosuppressive drugs on test performance. Translating these results into the clinical setting, false-negative results of CD154+ antigen-specific T-cell quantification need to be considered in patients receiving T-cell-active immunosuppressive medication. Optimized co-stimulation regimes with α-CD49d could contribute to an improved feasibility of functional T-cell assays in immunocompromised patient populations.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Antifungals; Aspergillus; Biomarker; CD49d; Flow cytometry; GvHD prophylaxis